Kompleksitas Operasi Perusahaan sebagai Pemoderasi Pengaruh Pergantian Auditor dan Financial Distress terhadap Audit Delay - Fatimah, Siti; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2018)
The purpose of this study was to determine the effect of auditor switching and financial distress on audit delay, as well as complexity of operations of the company as a moderating influence auditor switching and financial distress on audit delay. This research was conducted in consumer goods companies listed on the Indonesian Stock Exchange (BEI) of the year 2011- 2016. Samples taken as many as 156 companies using purposive sampling technique. The data collection was conducted using non-participant observation. The analysis technique used is Moderated Regression Analysis (MRA). Analysis results showed that auditor switching have no affect audit delay, while financial distress positively affect audit delay. Complexity of operations of the company was not able to moderate the relationship between auditor switching and financial distress with audit delay. Keywords: Audit Delay, Auditor Switching, Financial Distress, Complexity of Operations of the Company